The Impact of Embodied Cultural Capital (Subjective) on Intergeneration Social Mobility (Case Study: 30-54 Year-Old Citizens in Gorgan) - zahra ghafary (توسعه اجتماعی)
The purpose of this paper was intended to study the impact embodied cultural capital and intergenerational mobility of individuals in the city of Gorgan. The research method used in this study is suevey. For collecting the data, researcher-made questionnaire and for determining the reliability of the questionnaire, face validity technique and content validity with help of CVR coefficient technique and for determing the reliability of the questions, cronbach (alpha) coefficient were used. After questionnaire design and implementation of a pilot between 30 and responsive, questioning the reliability using Cronbach alpha coefficient (0/82). The sample of this study consisted of all women and men aged between 30 to 54 resident in Gorgan who were 146238 people based on 2011 census. The research sample size was 384 people. Multi-stage random sampling method was used to select. The samples. K-S test was used to identify the type of statistical method. In addition, parametric statistics (Pearson coefficient) was used for normal distribution of data. Descriptive results showed that 8.6 percent of responders were found to have descending intergenerational mobility, while 24 percent had horizontal intergenerational mobility and 67.4 percent enjoyed ascending intergenerational mobility. Finally, while studying the research hypothesis which is the relationship between embodied cultural capital (subjective) and intergenerational mobility of individuals in the city of Gorgan, it was approved at more -than- 95% confidence coefficient level.